2017
DOI: 10.1371/journal.pone.0185182
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq de novo assembly and differential transcriptome analysis of the nematode Ascaridia galli in relation to in vivo exposure to flubendazole

Abstract: The nematode Ascaridia galli (order Ascaridida) is an economically important intestinal parasite responsible for increased food consumption, reduced performance and elevated mortality in commercial poultry production. This roundworm is an emerging problem in several European countries on farms with laying hens, as a consequence of the recent European Union (EU) ban on conventional battery cages. As infection is associated with slow development of low levels of acquired protective immunity, parasite control rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…So far only two β-tubulin isotypes (isotype 1 and 2) have been described in Parascaris spp. [48], though more might be present in the genome since six putative β-tubulin genes were found in the closely related parasite Ascaridia galli [49]. It has also been mentioned that the Ascaris suum genome contains at least nine β-tubulin genes [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far only two β-tubulin isotypes (isotype 1 and 2) have been described in Parascaris spp. [48], though more might be present in the genome since six putative β-tubulin genes were found in the closely related parasite Ascaridia galli [49]. It has also been mentioned that the Ascaris suum genome contains at least nine β-tubulin genes [50].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the isoforms of ascarid β-tubulins should not be directly compared to the strongyle nematodes as phylogenetic studies have shown that they are evolutionary separated [48,49]. In a study by Martis et al [49], where the transcriptomes of A. galli were compared before and after in vivo exposure to flubendazole, Fig. 4 Venn diagrams showing the number of differentially expressed genes unique to and shared among Parascaris univalens worms exposed to three different concentrations of the anthelmintic drugs ivermectin (a), pyrantel citrate (b) and thiabendazole (c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nematodes, toxic chemicals activate the immune response and can change their fecundity and life span. RNA-Seq analyses demonstrated that some differentially expressed genes (DEGs) were related to the immune response ( Martis et al, 2017 ; Di et al, 2018 ). Changes of gene expression, in different life cycles, were detected by transcriptome sequencing ( Seiml-Buchinger and Matveeva, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been mentioned that the Ascaris suum genome contains at least nine β-tubulin genes (50). It should be noted that the isoforms of ascarid β-tubulins should not be directly compared to the strongyle nematodes as phylogenetic studies have shown that they are evolutionary separated (48,49). In a study by Martis et al (49) where the transcriptomes of A. galli were compared before and after in vivo exposure to flubendazole, no differential expression of β-tubulins was found, whereas a study by Tyden et al (51) showed an upregulation of β-tubulin isotype 1 in Parascaris spp.…”
Section: Discussionmentioning
confidence: 99%